TOWARDS REALIZING MALAYSIA’S SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS (STEM) INITIATIVES: PROFILING STUDENTS’ CONCEPTUAL UNDERSTANDING OF “OPERATIONS ON INTEGERS” - Khalid, Madihah; Ibrahim, Mohd Burhan; Othman, Joharry; Saad, Supiah; Mohd Yusuf, Yudariah; Embong, Zulmaryan (2019)
Previous studies have shown that students have difficulties and misconceptions in dealing with many areas of mathematics including in various topics of the number system such as integers. Students’ difficulty with the concept of integers causes them to struggle in solving mathematical problems, especially those involving the four basic operations. This study aims to diagnose students’ errors in the operations of integers, subsequent to validating the Errors Identification Integers Test (EIIT) which can identify the types of misconceptions that students possess in dealing with the operations of integers. The EIIT which consists of multiple-choice questions involving different combinations of positive and negative numbers was adapted to suit the Malaysian context. This study also determines whether there is any difference in terms of errors which may have been committed among students from rural and urban schools as well as gender. The population of this study is all Form One students from selected public schools in Peninsular Malaysia. A total of eight schools were involved in the data collection as samples. Cluster sampling was employed in order to ensure that the selected schools represented the population. The Rasch Model was used to improve and validate the instrument used in this study. In addition, teachers’ and students’ interviews were conducted to find and confirm the misconceptions of the operations of integers. Carelessness, poor knowledge, inability to assimilate concepts and surface understanding were identified as the types of misconceptions in this study. Meanwhile, this study found that parenthesis misapprehension, poor mathematical language, calculator hooking, superficial understanding and external limitation were the causes that led to the misconceptions. From the diagnostics test, it was determined that there was a significant difference between students’ performance in different areas (rural and urban) and gender.